The characterization of diffusion tensor for mid-latitude ionospheric plasma - Sagir, Selcuk; Yesil, Ali; Sanac, Gulay; Unal, Ibrahim (Ist Nazionale Di Geofisica E Vulcanologia, 2014)
In this study, the relationship between diffusion and the electrical conductivity tensor is investigated by using the real geometry of the Earth's magnetic field in the Northern Hemisphere for mid-latitudes. This relationship is derived from equation. Only in the elements of the diagonal of the tensor is an equal relationship found between the electrical conductivity called the longitudinal conductivity and the diffusion coefficient. The diagonal elements are equal to each other and do not depend on the Earth's magnetic field; however, the other elements of the tensor strongly depend on the Earth's magnetic field and they have characteristic of Bohm diffusion became a semi-empirical model (D-B= (1/16)kT/eB) but they do not depend on the electrical conductivity or the classical diffusion coefficient.